Inovasi Pelayanan Publik Papa Sehat Di SDN 81 Kalukubodo Kabupaten Takalar - Kartini, Nur Malitasari; Mahsyar, Abdul; Ma'ruf, Adnan (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study aimed to determine the PAPA SEHAT Public Service Innovation at SDN 81 Kalukubodo Takalar Regency and to know the supporting and inhibiting factors in the process of implementing the PAPA SEHAT Innovation. Data collection techniques used  observation, interview with 4 informants and documentation. Data analysis used interactive analysis models and used 3 types of triangulation in data validation. The results showed that this PAPA HEALTHY Innovation was implemented well in SDN 81 Kalukubodo, this was seen from the relative profit indicators that had been well, the appropriateness was appropriate with the presence, and the complexity was easily understood by children. Supporting factors in the implementation of PAPA HEALTHY Innovation was the support by the local government  in 2018 and  won the Top 40 award. Then the inhibiting factor was the presence of parents complained that children did not need to clean up at school because there was officers  who responsible even though doing the task hygiene outomatically children  used to behaving clean and healthy life in school, at home, and in the  environment of community